SWOT Analysis in The Indonesian Cosmetics Industry: a Systematic Literature Review with a Case Study of PT Paragon Innovation And Technology - Andrea Puteri; Suci, Fijria Rahma; Arissafia, Rizka Arsya; Panjaitan, David; Nisa, Khairun (Journal of Business and Behavioural Entrepreneurship, 2025)
The Indonesian cosmetics industry has shown significant growth in recent decades, driven by halal trends, awareness of active ingredients, and the influence of social media. This study aims to compile a Systematic Literature Review (SLR) of studies discussing the application of SWOT analysis (Strengths, Weaknesses, Opportunities, Threats) in the cosmetics industry, with a focus on PT Paragon Innovation and Technology as a case study. By examining 86 articles from various databases, this research identifies key findings related to strengths, weaknesses, opportunities, and threats in the cosmetics industry both globally and nationally. The analysis results show that Paragon possesses strengths in innovation, distribution, and commitment to halal cosmetics, but faces challenges in global competition and limitations in international expansion. This study also reveals research gaps in the aspects of global halal certification, utilization of digital technology, and the sustainability of MSMEs. This research provides theoretical and practical contributions to business strategy in the Indonesian cosmetics industry toward more sustainable competitiveness. Purpose: To compile a Systematic Literature Review (SLR) of various studies discussing the application of SWOT analysis in the cosmetics industry, with a focus on PT Paragon Innovation and Technology as a case study. Design/methodology/approach: systematic literature review; identification and synthesis of internal and external factors of the cosmetics industry (strengths, weaknesses, opportunities, threats). Finding: Paragon possesses strengths in innovation, distribution, and commitment to halal cosmetics, but faces challenges in global competition and limitations in international expansion. Keywords: Cosmetics industry, SWOT analysis, Paragon Paper type: A systematic literature review